- #1

- 5

- 0

Question: Show that i*r^i-(i-1)*r^(i-1) = r^(i-1)-(1-r)i*r^i-1. Use this result to find the sum of i*r^(i-1) from i=1 to i=n.

I've done the first part of this question, but need some help with the second. Thanks!

- Thread starter mathvision
- Start date

- #1

- 5

- 0

Question: Show that i*r^i-(i-1)*r^(i-1) = r^(i-1)-(1-r)i*r^i-1. Use this result to find the sum of i*r^(i-1) from i=1 to i=n.

I've done the first part of this question, but need some help with the second. Thanks!

- #2

MathematicalPhysicist

Gold Member

- 4,341

- 233

This identity isn't valid for i=1, check it.

- #3

HallsofIvy

Science Advisor

Homework Helper

- 41,833

- 961

Do you mean "i*r^i-(i-1)*r^(i-1) = r^(i-1)-(1-r)i*r^(i-1)"? Otherwise, as MathematicalPhysicist said, it is not true for i= 1.

Question: Show that i*r^i-(i-1)*r^(i-1) = r^(i-1)-(1-r)i*r^i-1. Use this result to find the sum of i*r^(i-1) from i=1 to i=n.

I've done the first part of this question, but need some help with the second. Thanks!

In any case, I would not use that. Are you required to?

I would note that [itex]\sum_{i=1}^n r^i[/itex] is a geometric sum and that [itex]\sum_{i= 1}^n i r^{i-1}[/itex] is its derivative with respect to r.

- #4

- 5

- 0

Yes it was a typo. And yes I'm required to use that result! :uhh:Do you mean "i*r^i-(i-1)*r^(i-1) = r^(i-1)-(1-r)i*r^(i-1)"? Otherwise, as MathematicalPhysicist said, it is not true for i= 1.

In any case, I would not use that. Are you required to?

I would note that [itex]\sum_{i=1}^n r^i[/itex] is a geometric sum and that [itex]\sum_{i= 1}^n i r^{i-1}[/itex] is its derivative with respect to r.

- #5

uart

Science Advisor

- 2,776

- 9

Hi mathvision, I've edited that for you.I wanted to post this in the homework forum, but there's only pre-calc for math.

Question: Show that

[tex]i r^i - (i-1)r^{i-1} = r^{i-1} - (1-r)i r^{i-1}[/tex]

Use this result to find the sum of [itex]i r^{i-1}[/itex] from i=1 to i=n.

I've done the first part of this question, but need some help with the second. Thanks!

If this isn't pre-calc then just differentiating the geometric series as Halls suggests is the best way to do it.

If this is pre-calc and you need to do it without using calculus then you can do the following. Sum both sides of your above expression and notice that the RHS is the sum of (r-1) times the sum you are trying to find, plus a simple geometric series. Also, the left hand side completely "telescopes", leaving just the first and last terms. Basically then you can just rearrange this to get an expression for the part you are interested in.

- Replies
- 6

- Views
- 1K

- Replies
- 5

- Views
- 1K

- Replies
- 7

- Views
- 6K

- Last Post

- Replies
- 6

- Views
- 424

- Last Post

- Replies
- 1

- Views
- 800

- Replies
- 4

- Views
- 929

- Replies
- 16

- Views
- 12K

- Last Post

- Replies
- 7

- Views
- 14K

- Replies
- 11

- Views
- 315

- Last Post

- Replies
- 7

- Views
- 3K